Mirhakym Zhavharovych Azyzov - "Orthopaedics, Traumatology; Prosthetics", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On December 5, 2019, after a long illness, the famous scientist orthopedic traumatologist, director of the Scientific Research Institute of Traumatology and Orthopedics of the Ministry of Health of the Republic of Uzbekistan, doctor of medical sciences, professor Azizov Mirkhakim Zhavkharovich passed away.